Association between prostate cancer development and TARBP1 - Wei Lui; Bilegtsaikhan Tsolmon; Ganbayar Batmunkh; Lai Fu Han; Shiirevnyamba Avirmed (Central Asian Journal of Medical Sciences)
Objective: Prostate cancer is the most frequent cancer among elderly men worldwide and second cause of cancer-related deaths in man. Prostate cancer characterized a clinically heterogeneous and genetic alterations in cells play a pivotal role in carcinogenesis. A detailed understandings of the genetic alterations in cancer cells are important for developing new therapeutic medicine. Transactivation response RNA-binding protein1 (TARBP1) encodes a protein with RNA-binding, tRNA methyltransferase activity, and RNA interference regulation functions, but its association with prostate cancer remains unclear. The aim of this study was to investigate clinical significance of TARBP1 in prostate cancer. Methods: Relative messenger ribonucleic acid (mRNA) and protein expression of TARBP1 in prostate cancer cell and tumor tissue was determined by qRT-PCR and Western blot analysis. LNCaP cells with lentivirus vector to silence the expression of TARBP1 were injected into nude mice. After 24 days, the mice were killed and tumor tissues were excised. The size of tumors was measured using a ruler and body weight of mice were weighed using a scale. Results: Through qRT-PCR and Western blot analysis, we validated that the expression levels of TARBP1 was decreased in TARBP1-knockdown prostate cancer cell compared with cells transfected with negative control LV-shNC RNA. The tumor growths were significant smaller in the group B (LNCaP-LV-shTARBP1) compared with group A (LNCaP-LV-shNC). Knocking down TARBP1 significantly suppressed the tumor progression of BALB/C nude xenograft. Moreover, body weight of mice in LNCaP-LV-shNC group increased significant slowly compared with LNCaP-LV-shTARBP1 group. The result of western blot analysis for TARBP1 in tumor tissues from xenograft nude mice bearing orthotopic LNCaP tumors shows that the expression of TARBP1 was also significantly decreased in the LNCaP-LV-shTARBP1 group compared with LNCaP-LV-shNC group (p < 0.05). Conclusion: We revealed that the TARBP1 highly expressed in prostate cancer and its role in promoting tumor growth. TARBP1 could serve as a potential therapeutic target for prostate cancer treatment and it is also a biomarker for tumor diagnosis and prognosis.